2021
DOI: 10.3389/fneur.2021.682729
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of COVID-19 and MS-Related Characteristics in a National Sample of People With MS in China

Abstract: Few studies have focused on immune status and disease activity in MS patients during the coronavirus disease 2019 (COVID-19) pandemic. The aim of this study is to investigate immune status, COVID-19 infection, and attacks in MS patients during the pandemic. An online questionnaire about COVID-19 infection, MS attack, and MS treatment during the pandemic was administered to all 525 MS patients registered in our hospital database from January 1, 2011, to June 1, 2020. Only 384 responded, of which 361 patients co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A large cohort from China suggested that relapse rates were determined mainly by MS itself and compliance to medications and not the pandemic ( Jj et al, 2020 ). Similarly, a study by Zhang reported increased MS relapses during the pandemic mostly in patients with poor compliance to DMT ( Zhang et al, 2021 ). Our study demonstrated a reduction in MS disease activities of up to 70 % during the pandemic, compared to the three years preceding the pandemic.…”
Section: Discussionmentioning
confidence: 84%
“…A large cohort from China suggested that relapse rates were determined mainly by MS itself and compliance to medications and not the pandemic ( Jj et al, 2020 ). Similarly, a study by Zhang reported increased MS relapses during the pandemic mostly in patients with poor compliance to DMT ( Zhang et al, 2021 ). Our study demonstrated a reduction in MS disease activities of up to 70 % during the pandemic, compared to the three years preceding the pandemic.…”
Section: Discussionmentioning
confidence: 84%
“…Since Multiple Sclerosis especially affects active, young adults and the treatment options include immunosuppressive drugs, developments related to COVID-19 are followed with curiosity and meticulousness by neurologists. Increasing number of studies had showed that the course of the COVID-19 disease in pwMS is similar to normal population with similar age and comorbidities, and there is no increase in the risk of developing the disease with effective preventive approaches 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…An important insight into relapse risk was presented in a study of Chinese pwMS, where a significant increase in relapse rate during the pandemic was observed, but only in those patients who experienced treatment discontinuation, dose reduction, or were not receiving any MS therapy [41].…”
Section: Recovery From Covid-19 In Ms Patientsmentioning
confidence: 99%